Telemedicine and Terminology: Different Needs of Context Information - Ingenerf, Josef (IEEE transactions on information technology in biomedicine : a publication of the IEEE Engineering in Medicine and Biology Society, 1999)
Traditionally, communication between healthcare providers, including the provision of physicians with information and knowledge, works quite well because there are implicitly common conventions and assumptions in the collaboration of all involved actors. The basic prerequisite of the communication process between humans is a mutual agreement on syntax and semantics of oral and written language, i.e., of the medical sublanguage. With telemedicine, i.e., the use of telecommunication and informatics in medicine, this prerequisite is no longer sufficient. First, various professionals from different clinical communities, characterized by specialty, nationality, school, etc., share the management of the patient's health. Second, electronically communicated information is more and more intended for processing by computer applications rather than for direct interpretation by human users. Third, the interconnection of distributed heterogeneous software systems in medicine raises the issue of semantic interoperability, especially the problem of data integration. A faithful communication in such a scenario must be based on explicit assumptions "behind" a message. Interpreting an usually highly context-dependent utterance demands for mechanisms on a pragmatic level in natural language processing. The need for additional processing and integration of the transferred data by the receiving system demands for standardization and mediation, taking into consideration contextual knowledge that cannot entirely be explained and processed with linguistic and terminological approaches. This paper describes different categories of contexts and also different needs of applications concerning "context awareness."
Keywords: Telemedicine; Terminology as Topic